Pharmacognostical, antioxidant and antiulcer screening of Cyclea peltata roots - Chellappan,David Raj (2011)
Cyclea peltata Hook. f. & Thomson, belongs to the family Menispermaceae commonly known as "paatha", is a climbing shrub found throughout South and East India. In Indian traditional medicine the tuberous roots are also used to treat jaundice, stomachache, fever and asthma. This study deals with the microscopic study of leafs and roots of C. peltata, along with the physico-chemical, preliminary phytochemical analyses and antioxidant properties. Acute oral toxicity study was conducted as per OECD-423 guidelines and the extract was found to be devoid of any conspicuous acute toxicity in extract treated animals and no mortality upto 2 g/kg by oral route. Hydroalcoholic extract of C. peltata in a dose dependant manner (125 and 250 mg/kg. p.o.) showed significant gastric protection against the ethanol-induced gastric ulcer model in rats.